2018
DOI: 10.1590/1678-5150-pvb-5137
|View full text |Cite
|
Sign up to set email alerts
|

Soropositividade e fatores de risco para leptospirose, toxoplasmose e neosporose na população canina do Estado da Paraíba

Abstract: RESUMO: Objetivou-se com este trabalho determinar a frequência de animais soropositivos para Leptospira spp., Toxoplasma gondii e Neospora caninum em cães do Estado da Paraíba, Nordeste do Brasil, bem como identificar fatores de risco. Foram amostrados 1.043 soros de cães procedentes de cinco centros urbanos considerados polos regionais: João Pessoa, Campina Grande, Patos, Sousa e Cajazeiras. Para o diagnóstico sorológico da infecção por Leptospira spp. foi utilizada a soroaglutinação microscópica (SAM) enquan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…Although other studies showed higher seropositivity rates in dogs that had contact with cattle than those that did not, this condition was not identified as a risk factor for N. caninum infection (MARTINS et al, 2012;FERNANDES et al, 2018). This study observed that dogs that had contact with cattle were 15.25 times more likely to present with anti-N. caninum antibodies.…”
Section: Discussionmentioning
confidence: 55%
“…Although other studies showed higher seropositivity rates in dogs that had contact with cattle than those that did not, this condition was not identified as a risk factor for N. caninum infection (MARTINS et al, 2012;FERNANDES et al, 2018). This study observed that dogs that had contact with cattle were 15.25 times more likely to present with anti-N. caninum antibodies.…”
Section: Discussionmentioning
confidence: 55%
“…The largest response with detectable IgG class antibodies was in females (56.25%). Regarding age, the frequency of positive animals was higher in the older ones (10 -12 years), which is expected by the higher chances of contact and exposure with other animals, and with the various risk factors for infection (35,38,41,42,44).…”
Section: Resultsmentioning
confidence: 91%
“…Working with 1043 serum samples from dogs from five urban centers of the State of Paraíba, with the objective of determining the frequency of seropositive animals for toxoplasmosis by IFAT, and other pathogens, Fernandes et al (38) Costa et al (41) evaluated the occurrence of T. gondii infection in dogs, in five regions, in the urban area of Botucatu-SP, by modified agglutination test (MAT) in 670 serum samples, and they found 58.6% females and 41.4% males positive for infection. Among infected dogs, 4.6% were less than one year old, and 95.4% were older.…”
Section: Introductionmentioning
confidence: 99%
“…Na fase aguda, pode ocorrer lesão hepática e renal, assim, os sinais como a azotemia, segundo sinal clínico mais relatado (49,06%), icterícia e anemia, podem ter relação com as alterações causadas pela espiroqueta nesses órgãos (SCHULLER et al, 2015;SYKES et al, 2011). O acesso à rua e o contato entre cães portadores favorece a transmissão da bactéria (BENITEZ et al, 2012;FERNANDES et al, 2018;MASCOLLI et al, 2016). Observou-se predomínio de infecção entre cães machos.…”
Section: Discussionunclassified